Ameliorative Activity of Ethanolic Extract of Artocarpus heterophyllus Stem Bark on Alloxan-induced Diabetic Rats - Basiru Olaitan Ajiboye; Oluwafemi Adeleke Ojo; Oluwatosin Adeyonu; Oluwatosin Imiere; Babatunji Emmanuel Oyinloye; Oluwafemi Ogunmodede (Tabriz University of Medical Sciences, 2018)
Purpose: Diabetes mellitus is one of the major endocrine disorders, characterized by impaired insulin action and deficiency. Traditionally, Artocarpus heterophyllus stem bark has been reputably used in the management of diabetes mellitus and its complications. The present study evaluates the ameliorative activity of ethanol extract of Artocarpus heterophyllus stem bark in alloxan-induced diabetic rats. Methods: Diabetes mellitus was induced by single intraperitoneal injection of 150 mg/kg body weight of alloxan and the animals were orally administered with 50, 100 and 150 mg/kg body weight ethanol extract of Artocarpus heterophyllus stem bark once daily for 21 days. Results: At the end of the intervention, diabetic control rats showed significant (p<0.05) weight reduction, abnormal haematological parameters, high serum lipids (except high density lipoprotein) concentrations, increased creatinine, bilirubin and urea levels with decreased in albumin level when compared with non-diabetic control rats. All these alterations were reverted to normal after administered with different doses of ethanol extract of Artocarpus heterophyllus stem bark most especially at 150 mg/kg body weight which exhibited no significant (p>0.05) different with non-diabetic rats. Conclusion: The results suggest that ethanol extract of Artocarpus heterophyllus stem bark may be useful in ameliorating complications associated with diabetes mellitus patients.